2005
DOI: 10.4319/lom.2005.3.326
|View full text |Cite
|
Sign up to set email alerts
|

The dissolved organic iodine species of the isotopic ratio of 129I/127I: A novel tool for tracing terrestrial organic carbon in the estuarine surface waters of Galveston Bay, Texas

Abstract: Variations in 129 I/ 127 I ratios were used to trace terrestrial organic carbon (tDOC) across an estuary because (1) iodine is biophilic, up to 75% of total iodine in fresh and coastal marine waters partitions into organic iodine; (2) 129 I/ 127 I ratios in tDOC are greatly elevated over those from marine systems because atmospheric emissions of 129 I from European nuclear fuel reprocessing facilities were mixed more quickly in the surface ocean, up to 500 m in a decade, than the terrestrial system, which mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 41 publications
4
44
0
Order By: Relevance
“…However, organic 129 I cannot be determined in this procedure. Schwehr et al [17] proposed a procedure for the determination of organic I may be significant comparing to iodide and iodate for which the procedure described above can be also used.…”
Section: Speciation Analysis Of 129 I In Environment and Its Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, organic 129 I cannot be determined in this procedure. Schwehr et al [17] proposed a procedure for the determination of organic I may be significant comparing to iodide and iodate for which the procedure described above can be also used.…”
Section: Speciation Analysis Of 129 I In Environment and Its Applicationmentioning
confidence: 99%
“…129 I is one of key radionuclides in the nuclear waste depository, 129 I has also been shown a very useful isotope for the age dating [4,5], a suitable oceanographic tracer for studying transport and exchange of water mass [6][7][8][9][10][11][12][13][14][15], as well as a useful environmental tracer for investigating geochemical cycle of stable iodine [16][17][18][19]. Knowledge on the speciation of 129 I is a key issue for safety assessment of radioactive waste repositories, for estimation of human exposure through multiple pathways, as well as its application as an environmental and oceanographic tracer.…”
Section: Introductionmentioning
confidence: 99%
“…Speciation analysis of iodine was mainly done on stable 127 I (Hou et al, 1997;dela Veija et al, 1997;Sanchez & Szpunar, 1999;Hou et al, 2000c;Leiterer et al, 2001;Schwehr & Santschi, 2003;Shah et al, 2005;Gilfedder et al, 2008), with some studies on 129 I (Hou et al, 2001;Hou et al, 2003b;Schwehr et al, 2005;Englund et al, 2010b). Majority of researches performed on 127 I and 129 I are limited to fractionations of iodine -water soluble, exchangeable, bound to oxides, organic-inorganic fraction, etc.…”
Section: Factors Affecting Biogeochemical Cycling Of Iodinementioning
confidence: 99%
“…However, our own measurements of groundwater from several of the F-area aquifer bore holes found that organo-iodine could account for up to 25% of total iodine (43,52). The various isotopes of iodine can be strongly bound to macromolecular organic matter, which can significantly decrease or increase its transport, bioavailability, and transfer to humans, depending on the molecular weight and physicochemical properties of the resulting iodine-organic matter species (15,19,(41)(42)(43)49).…”
mentioning
confidence: 99%